2017
DOI: 10.1088/1757-899x/217/1/012011
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of efficiency of solar panel by phase change material cooling

Abstract: Abstract. The dependence of efficiency of photovoltaic panels on their temperature during operation is a major concern for developers and users. In this paper, a phase change material (PCM) cooling system was designed for a 60W mono-crystalline solar panel. Tealights candle was selected as the cooling medium. The solar irradiance was recorded using Kipp & Zonen CMP3 pyranometer and Meteon data logger. Temperature distribution on the surface of solar panel, output voltage and output current of solar panel were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…For instance, Stropnik and Stritih [7] identified that one major reason which significantly influences Photovoltaic (PV) solar panel efficiency is the working or panel surface temperature. Tan Jian Wei et al [8] in another study demonstrated that temperature has an adverse effect on the cell efficiency as, if the temperature of solar cells is increased, the energy conversion of the module is decreased. Moharram et al [9] specifically mentions that the efficiency of the module drops with the rise in temperature with the rate of approximately 0.5%/˚C.…”
Section: State Of the Art Technologiesmentioning
confidence: 99%
“…For instance, Stropnik and Stritih [7] identified that one major reason which significantly influences Photovoltaic (PV) solar panel efficiency is the working or panel surface temperature. Tan Jian Wei et al [8] in another study demonstrated that temperature has an adverse effect on the cell efficiency as, if the temperature of solar cells is increased, the energy conversion of the module is decreased. Moharram et al [9] specifically mentions that the efficiency of the module drops with the rise in temperature with the rate of approximately 0.5%/˚C.…”
Section: State Of the Art Technologiesmentioning
confidence: 99%
“…While the input power (Pin) is the amount of solar radiation in units (W/m 2 ) multiplied by the surface area of the PV in units (m 2 ) [25], as shown by (3):…”
Section: Empirical 231 Efficiency Of Photovoltaicsmentioning
confidence: 99%
“…Polycrystalline solar panels have an efficiency of 15.5-18%, and monocrystalline solar panels have an efficiency of 18.5 to 23.5%. However, monocrystalline solar panels have a higher cost, which is due to the fact that monocrystalline panels use monocrystalline silicon with a very high degree of purification above 99.99% [5,6].…”
Section: Introductionmentioning
confidence: 99%